Exploring and visualizing co-patent networks in bioenergy field: A perspective from inventor, transnational inventor, and country. Issue 5 (9th April 2022) - Liu, Weiwei; Li, Fangye; Bi, Kexin
ABSTRACT: Bioenergy is an important renewable energy source. Its development depends more on technological innovation, especially collaborative innovation. As patent data shows the latest technological progress, it is considered to be one of the indicators describing technological innovation. This paper analyzes the accumulation process of bioenergy technology innovation capabilities in different countries or regions from the perspective of co-patents. We collected all co-patents in bioenergy field in the European Patent Office (EPO) from 1976 to 2018, and used social network analysis to visualize the nodes, clusters and their relationships in the inventor, transnational inventor and country co-patent networks. The empirical results indicate that the number of co-patents has noticeably increased since 2008. The most common technology areas comprise biofuels, biochemistry and enzymology. China has the largest number of co-patents in bioenergy field and it is prominent in the inventor co-patent network. The United States is more important in the transnational inventor co-patent network and the country co-patent network, and both are dominant. The research on the status of co-patents can provide a new perspective for technological innovation, which will help make future technology planning of different countries more rationally.